Advancing child health and educational equity during the COVID-19 pandemic through science and advocacy - Rachel Gur-Arie; Sara Johnson; Megan Collins (BMC, 2022)
Abstract The COVID-19 pandemic has underscored the changing role of scientists, clinicians, ethicists, and educators in advocacy as they rapidly translate their findings to inform practice and policy. Critical efforts have been directed towards understanding child well-being, especially with pandemic-related educational disruptions. While school closures were part of early widespread public health measures to curb the spread of COVID-19, they have not been without consequences for all children, and especially for children from disadvantaged backgrounds. In a recent Isr J Health Policy Res perspective, Paltiel and colleagues demonstrate the integral role of academic activism to promote child well-being during the pandemic by highlighting work of the multidisciplinary academic group on children and coronavirus (MACC). In this commentary, we explore parallels to MACC's work in an international context by describing the efforts of a multidisciplinary team at Johns Hopkins University in Baltimore, Maryland, United States, to aggregate data, conduct analyses, and offer training tools intended to minimize health and educational inequities for children throughout the COVID-19 pandemic. As both MACC and our work collectively demonstrates, multidisciplinary partnerships and public-facing data-driven initiatives are crucial to advocating for children's equitable access to quality health and education. This will likely not be the last pandemic that children experience in their lifetime. As such, efforts should be made to apply the lessons learned during the current pandemic to strengthen multidisciplinary academic-public partnerships which will continue to play a critical role in the future.